Sejauhmana Tanggung Jawab Notaris terhadap Surat Dibawah Tangan yang di Daftarkan pada Buku Khusus Notaris (Waarmerking) - Marchellino Fortuna Kano; Khusnul Yaqin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
In conducting a Notary position, the Notary is required to be able to know the responsibilities and authority of the Notary in performing his/her position in accordance with the Notary Position Law. One of them is the authority of the Notary in Law Number 30 of 2004 concerning the Notary Position jo Law Number 2 of 2014 in Article 15 paragraph 2 letters a and b